Long-term trends in the epidemiology of cardiovascular diseases in the UK: insights from the British Heart Foundation statistical compendium. Issue 10 (14th April 2022) - Cheema, Katherine Margaret; Dicks, Ed; Pearson, Jeremy; Samani, Nilesh J
Abstract: The British Heart Foundation's (BHF) annual statistical compendium is a comprehensive source of accessible epidemiological data in relation to cardiovascular disease (CVD) in the UK. Using datasets with multiple years of data from the compendium we have analysed trends in mortality, morbidity, and treatment for CVD within the UK. CVD mortality in the UK has consistently declined over recent decades, from 1045 deaths per 100 000 in 1969, shortly after the BHF was founded, to 255 per 100 000 in 2019. Despite this remarkable improvement, inequalities in CVD mortality persist in the UK nations, for example in 2019 the death rate in Scotland was 326 deaths per 100 000 compared with 246 per 100 000 in England. Improvements in CVD mortality have been paralleled by increased use of primary prevention medications (anti-hypertensives and statins) and interventional procedures. In recent years, progress in mortality outcomes has stalled, probably due to a combination of factors including a rise in risk factors such as obesity and diabetes. In terms of morbidity, CVD remains a significant burden in the UK, accounting for at least 1.18 million hospital admissions and reflects the enormous economic burden of CVD, estimated at £19bn in the UK. Our results highlight the importance of accessible and comprehensive statistics in relation to the burden of CVD and the value of the BHF's annual compendium in drawing out conclusions and opportunities for future research. One key area is to improve the data on which estimation of prevalence is based. There is also a need for ongoing work to better understand the root causes of disparity between socio-economic groups in relation to CVD. One important way to address this will be to improve the consistency of reporting of CVD health data across all nations of the UK. Understanding the causes will inform UK healthcare planning in addition to providing analytical insights that will be applicable in other countries.